Broadband Metamaterial Absorbers for Organic Solar Cells: A Review - Kakil, Diyaree O.; Muhammadsharif, Fahmi F.; Abdulkarim, Yadgar I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Organic solar cells (OSCs) often suffer from weak absorption in the visible and infrared spectrum, which directly restricts their efficiency. Since light harvesting is central to solar conversion, improving absorption across a broad range is critical. Broadband metamaterial absorbers (BMMAs) present a promising solution by enhancing light-matter interaction and extending absorption over a broader spectrum. This improvement directly makes the process of converting energy more efficient. This review aims to systematically examine the recent progress of metamaterial absorbers (MMAs), highlighting broadband, polarization independent, and wide-angle designs areas that remain unexplored in recent reviews. Different categories of strategies, such as planar, vertical, lumped-element, and nanostructured plasmonic designs, are discussed to highlight how material choice and design geometry affect absorption. In addition, it describes the physical concepts of perfect absorption and assesses how applicable they are to OSC integration. Our analysis shows that the most of the progress has been theoretical approaches with a limited experiment. These studies demonstrate that BMMAs have an excellent opportunity to significantly improve energy conversion efficiency. At the same time, most challenges remain, like scalability, material losses, and easy integration into OGCs. This research also points out that there are future investigations into affordable, low-loss materials that can be easily integrated. Overall, this study emphasizes how important MMBAs are to advancing the efficiency and sustainability of next generation OSCs.